Duke Ellington the piano prince and his orchestra - Pinkney, Andrea Davis; Pinkney, J. Brian (New York Jump at the Sun/Hyperion Paperbacks for Children, 2007)
A brief recounting of the career of this jazz musician and composer who, along with his orchestra, created music that was beyond category.
"A Caldecott honor book."
Keywords: Ellington, Duke -- 1899-1974 -- Juvenile literature; Jazz musicians -- United States -- Biography -- Juvenile literature; Musicians; African Americans -- Biography